PERAN HAKIM DALAM MENEGAKAN KEADILAN DALAM PROSES PENEGAKAN HUKUM PIDANA - Triadi, Triadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Judges play a highly central role in adjudicating criminal cases. They are not only interpreters of the law but also guardians of justice, legal certainty, and human rights. In the Indonesian judicial system, judicial authority is guaranteed by the Constitution; however, in practice, the role of judges continues to face a number of serious challenges. First, judicial independence remains vulnerable to political intervention, media pressure, and other forms of power. Second, the quality of evidence assessment and the application of law are still not optimal, with a dominance of testimonial evidence and limited use of scientific evidence. Third, lengthy judicial processes harm the rights of both defendants and victims. Fourth, judicial integrity and ethics remain critical issues, as cases of corruption and violations of the code of ethics continue to occur. Fifth, judges’ understanding of law and technology needs to be improved. Sixth, the protection of defendants’ rights has not been fully guaranteed. Seventh, inconsistency in court decisions and the dominance of a retributive system reduce public trust. Therefore, although the judicial system has undergone reforms, the role of judges still requires strengthening in terms of institutional structure, quality, and integrity. Keywords: Judges, Justice, Law Enforcement.